Determinants of bank's profitability in Malaysia / Nurshahira Abd Samad - Abd Samad, Nurshahira (2022)
Banks play a vital role in the countries and economies of the world. Profitability and efficiency are key elements for banks since they help to the financial system's stability and safeguard a country from unfavorable waves. Therefore, it is necessary to understand the factors influencing commercial banks' profitability. The main purpose of this research is to study the Determinants of Bank's Profitability in Malaysia. This research is performed using the most popular measurement tool that is Return on Asset (ROA) to examine the relationship between net interest margin, bank loan, net profit, bank size, and credit risk to bank profitability. Data collected for this analysis was obtained from the bank's annual reports. This study uses secondary data from the top five (5) commercial banks listed in Bursa Malaysia between the year 2015 to 2020 and a total of 30 years of study duration. This study uses panel data to examine the collected data and regressed using the Pooled Ordinary Least Square Model. The results of this study are focused on descriptive analysis, correlation analysis, regression analysis, and test on assumptions. Therefore, based on the study it is concluded that there is a relationship between the variables with bank performance.